FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEKAMBUHAN PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU - Suchy " Ramadhanis; Fathra Annis Nauli; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract  The purpose of this research is to determine the factors that influence relapse in patients with Schizophrenia in Tampan pscychiatric hospital province riau. This research used descriptive correlation design with cross sectional approach. This research was conducted at Tampan pscychiatric hospital province riau with 71 people who experienced a relapse of Schizophrenia and taken through purposive sampling by taking into account the inclusion criteria. The measuring instrument was questionnaire that had been tested for validity and reliability. The analysis used are univariate and bivariate used alternative Fisher’s Exact  test. The result of this research showed that there are significant relationship between order taking medication (p value = 0,000) with patients relapse, and that there are significant relationship between the side effects of drugs (p value = 0,000), family support (p value = 0,002) with patient’s relapse. The result of this experiment recommend to hospital institutions to improve the delivery of nursing care anda health promotion to patient’s undergoing treatment in the clinic and help direct the adaptive coping mechanisme, as well provide support and explanation of the procedure to be passed by the patient so that the patient does not occur again relapse. Keywords : familly support, order taking medication,  relapse schizophrenia, the side effects of drugs